DETERMINATION OF GENETIC DISTANCE BETWEEN TURKISH SHEEP BREEDS WITH VARIOUS METHODS USING SOME BLOOD PROTEIN LOCI - M. Ozdemir; O. C. Bilgin; N. Esenbuga (Journal of Animal and Plant Sciences, 2011)
This study was conducted to estimate genetic distances among Akkaraman, Morkaraman, Awassi, Merino, Karakul, Kivircik, Imroz, Daglic and Karayaka sheep breeds reared in Turkey based on simple polymorphic blood protein types by using various methods including horizontal strach gel electrophoresis and polyacrilamyde gel electrophoresis (PAGE). NJ and UPGMA trees were constructed based on genetic distances computed by Nei, Cavalli-Sforza and Reynolds methods. Phylogenetic trees constructed on the polymorphic systems of the populations using the methods of Nei and Reynolds were found similar whereas Cavalli-Sforza was different figure. All the trees produced by method of UPGMA exhibited two large clusters of sheep populations but NJ method yielded small groups of the breeds. As a result that we have seen on the phylogenetic tree diagrams the fat-tailed sheep were clearly separeted from the others.
Keywords: Blood polymorphism; Sheep; Genetic diversity; Phylogenetic tree.